Ujaran Kebencian Di Media Sosial Perspektif Hukum Islam dan Hukum Positif Di Indonesia - Ahmad Badrut Tamam (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2021)
Everyone has the right to express opinions through various media, including social media. But some people use social media to express negative things, including hate. The appearance of hate speech acts can cause hatred and attack the honor of other individuals or groups. An in-depth assessment is needed regarding hate speech in the view of Islamic law and positive law. The problem studied by the author is how the views of Islamic law and positive law on hate speech acts are carried out on social media. The purpose of this paper is to find out hate speech through social media in the view of Islamic law and laws relating to information and electronic transactions in Indonesia.